Impact of innovation and high-tech trade on national competitiveness and employment structure - Idris, Zera Zuryana (2021)
According to the present trend, developing countries are progressively becoming the leading high-tech exporters. Growing high-tech exports from emerging countries has prompted concerns about their participation in the lowest fragment of the global value chain. Participating in the lowest segment may delay the catch-up process for developing countries and prolonging the income convergence between economies. As argued by the literature, innovation activities are not extensive at this stage. Hence, it may not be a requirement for high-tech export. Furthermore, statistics demonstrate a decrease in high-tech exports from developed countries, despite significant innovative investment. Hence, this leads to the questioning of the role of innovation in high-tech exports. Despite the anticipated gains of high-tech trade, the competitiveness of high-tech exporters remains low. Also, the reduction in employment is noticeable along with the increase in high-tech trade. Drawing upon this scenario, this research aims to study the role of innovation on high-tech trade and the implication of high-tech trade. This research is using a sample of 20 major high-tech exporting countries. The time span for this study is from 2007 to 2016. This research has three specific objectives. The first objective of this research is to analyse the impact of innovation on the high-tech trade. Departing from the existing literature, this study also examines the impact of innovation on the extensive margin of high-tech trade. The empirical analysis is conducted based on the gravity model of trade. Empirically, an increase in domestic research and expenditure (R&D) expenditure by one percent will induce high-tech exports value to grow by 0.34 percent and numbers of exported products by about 0.08 percent, respectively. The second objective of this study is to examine the impact of high-tech trade on national competitiveness. The empirical analysis was done using panel data estimation technique including the Bias-corrected Least Square Dummy Variable (LSDVC). An increase in high-tech trade by one percent increases national competitiveness by 0.09 index point. The third objective of this research is to study the impact of high-tech trade on employment structure. The LSDVC estimation technique was employed to estimate this impact. A one percent increase in high-tech trade increases the share of employment for the high-skill worker by 0.05 percent and reduces the share of employment for the middle-skill worker by 0.03 percent. The positive impact of R&D expenditure on high-tech export suggests that the domestic investment in innovative activities is crucial to support the development of the high-tech industry. Tax incentives and other policies to encourage innovation such as research collaboration are needed to enhance high-tech exports. High-tech trade also boosts national competitiveness. High competitiveness enhances economic growth, income levels, and people's standard of living. Hence, policy should be formulated in a way that can promote high-tech trade. However, the expansion of high-tech trade may harm certain segments of the labour market. It reduces the demand for the middle skilled worker. The shrinking of demand may suppress their wages and widen the inequality in the society. This will harm the process of achieving sustainable development. The policy to develop the high-tech industry must be accompanied by an appropriate labour policy such as an upskilling program. Even though high-tech trade may enhance the living standard of the people, the unintended effect of its expansion must be taken into consideration.